Hermeneutyka trydenckiej doktryny na temat mszy świętej w perspektywie katolickiego tradycjonalizmu = Hermeneutics of the Tridentine Doctrine on the Mass in the Perspective of Catholic Traditionalism - Lisak, Marcin (Studia religiologica, 2015)
The Council of Trent defined what the Eucharistic conversion is, and classified some liturgical questions concerning the order of Holy Mass and its sacrificial nature. Regarding this, groups of traditionalist Catholics claim that such definitions must be treated as a perfect, crowning, and unalterable way of orthodoxy. Nonetheless, an in-depth analysis shows that the Tridentine doctrine and discipline are far more “open” than “hermetically sealed”. The Eucharistic Tridentine terminology, however, is predominantly symbolical, that is characteristic of communication in religion, but not only abstract or strictly metaphysical. Furthermore, the disciplinary research solutions are rather historical and apologetic than universal or unchangeable. In consequence, the article proves that a hermeneutical approach is essential in analysis of Christian tradition and doctrine.